Minimizing the Cost of Treating Asymptomatic Ureterolithiasis. Issue 3 (May 2018) - Lamberts, Remy W.; Lines, Emily; Conti, Simon L.; Leppert, John T.; Elliott, Christopher S.
Abstract : Introduction: : Treatment of patients with ureterolithiasis who report resolution of their symptoms but do not recall passing the stone presents a clinical challenge. We analyzed the cost of different therapeutic strategies for these patients. Methods: : We performed a cost minimization analysis using published efficacy data and Medicare reimbursement costs. We compared 1) up‐front ureteroscopy with planned lithotripsy, 2) followup imaging to determine presence or absence of stone using computerized tomography, abdominal plain film or ultrasound and 3) observation. We performed sensitivity analyses on the factors driving cost, including the probability of stone passage and ultrasound sensitivity. Results: : Observation was associated with the lowest costs for patients likely to spontaneously pass the ureteral stone (greater than 62%). Initial imaging with computerized tomography was the least costly approach for patients with an intermediate probability of stone passage (21% to 62%). When the sensitivity of ultrasound was modeled to be high (greater than 79%), it surpassed computerized tomography as the least costly approach across a wide range of spontaneous passage rates. Ureteroscopy was associated with the lowest costs when the probability of spontaneous stone passage was low (less than 21%). Conclusions: : The probability of spontaneous passage of a ureteral stone can be used to optimize treatment strategies for patients. Observation minimizes costs for patients with stones likely to pass spontaneously, whereas ureteroscopy minimizes costs for stones unlikely to pass. For ureteral stones with an intermediate probability of spontaneous passage computerized tomography to guide treatment is associated with the lowest estimated costs.